2,4,6,8-Tetraiodoglycoluril in sulfuric acid as a new powerfulreagent for iodination of deactivated arenes; Tetrahedron Letters; Vol. 41, iss. 47 - Chaikovskii V. K. Vitold Kazimirovich; Filimonov V. D. Viktor Dmitrievich; Yagovkin A. Yu.; Kharlova T. (2000, 2000)
Deactivated arenes are iodinated readily at 0°C by the action of 2,4,6,8-tetraiodoglycoluril in sulfuricacid to give the iodoarenes in generally good yields.